Facility based retrospective infant death study in a tertiary care hospital of Tripura - Baidya, Subrata; Debbarma, Sanjib; Paul, Debosmita; Chowdhury, Purvita; Kalita, Biraj Kumar; Karmakar, Sanjoy (International Journal Of Community Medicine And Public Health, 2020)
Background: Infant and neonatal mortality are important indicators of the overall physical health of a community. An increase is generally indicative of unmet human needs in healthcare, sanitation, nutrition and education. Objective: To estimate the different causes of death along with the geographic distribution of the reported death cases during the study period. Methods: Analysis of the retrospective mortality data of infant and neonates in the Pediatric Department of Agartala Government Medical College and Hospital, from 2014-2018, was conducted. Results: A total of 1525 infant deaths were recorded in the study facility, of which 878 (57.57%) were early-neonates, 120 (7.87%) late neonates and 527 (34.56%) post-neonatal infants. The most reported causes of neonatal mortality in Tripura were found to be preterm/low birth weight and perinatal asphyxia with OR of 1.45 (CI=1.137-1.857) and 1.41 (CI=1.10-1.81) respectively. Conclusions: The increasing burden of preterm births and neonatal sepsis needs attention towards ante-natal care along with holistic healthcare services. The need for intensive actions from both administration and healthcare facility to promote identification of red-flags at primary level, followed by proper referral from the periphery to tertiary care facility has been reiterated in this study.